An Action-Level Assistant for Robotic Manipulation: User Experience and Performance - Martins, Diogo; Aldhaheri, Sara; Kopanev, Pavel; Pairet, Èric; Ardón, Paola; Sá, Alirio (Anais do Simpósio Brasileiro de Engenharia de Sistemas Computacionais (SBESC), 2023)
Achieving full autonomy in robotic manipulation tasks in unstructured environments remains challenging despite technological advancements. This paper introduces LOLA, a user-centric framework designed for seamless task creation across various robotic manipulators. A comparative user study with 20 participants revealed that LOLA closely matched user’s expectations highlighting its potential for broader application in robotic manipulation.